Impact of the first-pass pulmonary vein isolation on ablation outcomes in persistent atrial fibrillation - Luo, Chenxu; Leng, Bing; Yu, Xinzhi; Du, Xianfeng; Chu, Huimin; Zhou, Shenyuan; Shen, Caijie; Feng, Mingjun; Jiang, Yongxing; Jin, He; Fu, Guohua; Yu, Lipu; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe achievement of first-pass isolation (FPI) during pulmonary vein isolation (PVI) generally serves as a reliable marker of lesion quality in initial radiofrequency encirclement and predicts favorable procedural outcomes. This study sought to evaluate the impact of the FPI on the long-term clinical outcomes in persistent atrial fibrillation (PeAF) patients undergoing radiofrequency ablation.MethodsWe conducted a retrospective analysis of 346 patients with PeAF who were divided into three groups: patients with FPI in bilateral PVs (BOTH group, n = 197), those with FPI in either ipsilateral PVs (EITHER group, n = 92), and those without FPI in bilateral PVs (NEITHER group, n = 57). Achieving FPI in at least one of the two ipsilateral PVs (at least ipsilateral FPI, IFPI) was utilized as a metric for evaluation. The primary endpoint was freedom from atrial tachyarrhythmias (ATAs) lasting longer than 30s beyond the blanking period. Baseline characteristics, procedural results and long-term clinical outcomes were compared among the groups.ResultThe FPI was effectively achieved in 251 left PVs (72.5%) and 235 right PVs (67.9%). After a median follow-up of 658(402, 970) days, the NEITHER group exhibited less freedom from ATAs recurrence than the BOTH group (57.9% vs. 75.1%, P < 0.001) or the EITHER group (57.9% vs. 70.7%, P = 0.036). IFPI was an independent predictor of freedom from ATAs recurrence in PeAF patients undergoing their initial ablation (HR, 0.46; 95% CI, 0.29–0.74; P = 0.001).ConclusionAchieving FPI for PVI remained a significant association with improved ablation outcomes in PeAF patients, wherein IFPI served as an important determinant.